Results of the Implementation of a Tool for the Stratification and Management of Diabetic Patients with Uncomplicated Acute Hyperglycemia in the Emergency Department - Luis Alberto Corona Martínez; Laydamí Rodríguez Amador (Medisur)
Background: decompensated diabetes is a common cause of visits to emergency departments. Objective: to describe the introduction and validation of a tool for the stratification and management of diabetic patients with uncomplicated acute hyperglycemia in the Emergency Department. Methods: the experimental application of the tool was conducted from February through June 2014 involving 202 patients. Several process and outcome indicators were used for its assessment. Results: diagnosis was reached through blood tests in 97% of cases. There was a gradual increase of stratification per month; most patients were classified into groups one and two. Classification was correct in only 70% of the cases. Adherence to the suggested initial procedures was low (57%), which was determined by the outcomes in the group two (13%) since most of the patients were not admitted to the observation ward. Adherence to insulin therapy was higher (67%). Adherence to the recommended follow-up was low due to early discharge of patients. The resolution rate in the emergency services was 93%. Only one case of hypoglycemia was registered. No patient developed any other serious metabolic complication. Resolution of the condition in the yellow zone of the emergency department was high regardless of being in the group one or two. No other serious metabolic complications were observed. Conclusions: continuation of the stratification of diabetic patients with uncomplicated acute hyperglycemia in the Emergency Department is recommended, with modifications to the stratification tool in the groups one and two and the time for clinical and laboratory reassessment.